Pengaruh Brand Ambassador, Review Online Youtube, Pengalaman Belanja Online, Persepsi Kemudahan, Dan Persepsi Risiko Terhadap Minat Beli Di Tiket.Com Pada Masa Pandemi Covid-19 Di Kota Malang - Muhammad Anshor Syafi’i; Rois Arifin; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe goal of this study is to pinpoint and examine factors that simultaneously and partially influence consumers' intent to make purchases at Tiket.com, including brand ambassadors, online reviews posted to YouTube, online shopping experiences, perceived convenience, and risk perceptions. The independent variables in this measurement are Brand ambassador, YouTube Online Review, Online Shopping Experience, Perception of Ease, and Perception of Risk, while the dependent variable is buying interest. Quantitative research using a descriptive methodology is the sort of research used in this study. From the outset to the creation of the study design, the quantitative research method's specifications are systematic, well-planned, and clearly defined. The SPSS program's multiple linear regression analysis tool was used to manage the data. The data used includes both primary and secondary data that were gathered through surveys, interviews, and both direct and indirect observations. Since the sample size for this study is unclear, the maholtra calculation with data  24 indicators multiplied by 5 results in 120. The analysis of the data revealed that the variables of brand ambassador, youtube online review, online shopping experience, perceived convenience, and perceived danger simultaneously and partially influence the purchasing intentions of Tiket.com users in Malang City. Keywords: Purchase Intention. Brand Ambassador, Online Yotube Review, Online Shopping Experience, Easy Perception, And Risk Perception